MANAJEMEN REKRUTMEN, SELEKSI, ORIENTASI DAN PENEMPATAN SUMBER DAYA MANUSIA PENDIDIKAN BERBASIS NILAI-NILAI ISLAM - Muhammad Fendra Kari; Amirudin Muslim; Arif Irawan; Palah; Rusi Rusmiati Aliyyah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine human resource management practices at SMK Amaliah 1 Ciawi, with a particular focus on the recruitment, selection, orientation, and placement of teaching and administrative staff. A qualitative method was employed through interviews with three key informants: the principal, the vice principal for curriculum, and the head of administration. The findings reveal that recruitment is carried out systematically based on institutional needs, with the selection process emphasizing professional competence and Islamic values. Orientation programs are regularly implemented through In-House Training (IHT), while staff placement considers educational background and school needs. Performance evaluation is conducted informally through meetings and direct supervision. The main challenge identified is the limited availability of vocational human resources that meet the required qualifications. The study recommends strengthening digital documentation systems, adaptive mentoring, and partnerships with higher education institutions